Hubungan Masalah Emosi dan Perilaku dengan Pola Asuh, dan Relasi Keluarga pada Anak Sekolah Dasar - Surilena Hasan; Adela Teresa; Nelly Tina Widjaja (Jurnal Kedokteran Meditek, 2023)
Emotional-behavioral problems in children can manifest as negative behaviors and self-concepts. Parenting patterns and family relationships have an essential role in preventing emotional-behavioral problems in children, and both can prevent their occurrence. An essential role in emotional-behavioral problems in children, and both can prevent their occurrence. and SDN 10) in Penjaringan Subdistrict, North Jakarta. A cross-sectional study was conducted from August to December 2019, involving 231 parents of public elementary school students in the Penjaringan Subdistrict who met the inclusion and exclusion criteria. Data were analyzed by univariate and bivariate analysis using SPSS 22.0. Elementary school students are in grades 4, 5, and 6, aged 10–14 years; 53.2% are male, and 11.7% of children have emotional behavior problems. This study shows that 18.7% of students with exposure parenting have emotional-behavioral problems, and 10.8% of children with extreme family relationships have emotional-behavioral problems. The bivariate analysis test (chi-square test) showed a significant relationship (p = 0.000) between emotional-behavioral problems and family relationships. Therefore, parents need to evaluate and increase awareness of the critical role of parents in the physical, psychological, and social development of children, especially in maintaining the quality of family relationships.